Systematic search for the presence of mesocarnivores in the Foz de Arbaiun Nature Reserve (Navarra, Spain) - Gil, Carmen; Vela, Imanol (Revista Ciencia Agraria, 2022)
The order of carnivores plays a fundamental role in regulating the food chain. The complex has been the historical relationship it has had with the human being, and its fight against "vermin" by hunting species highlights that more profound knowledge of these species is necessary to favor their conservation. This study conducted a systematic search of the different species of carnivores in the Foz de Arbaiun Nature Reserve (Navarra). The species searched for were weasel (Mustela nivalis), stoat (Mustela erminea), polecat (Mustela putorius), European mink (Mustela lutreola), American mink (Neovison vison), stone marten (Martes foina), marten (Martes Martes), badger (Meles meles), otter (Lutra lutra), genet (Genetta genetta) and fox (Vulpes vulpes). Two sampling methods were used. On the one hand, transects were used, where almost the entire extension of the Reserve was covered in search of traces: footprints, droppings, hair, and burrows. On the other hand, photographic trapping was also used, installing cameras of this type in the mouth. Traces of weasel, stoat, badger, otter, genet, and fox were found from the binomial formed by stone marten and marten and from the group formed by polecats, American mink, and European mink.
Keywords: systematic search; mesocarnivores; track; transect